Preparation of alginate–chitosan fibers with potential biomedical applications. (10th December 2015) - Sibaja, Bernal; Culbertson, Edward; Marshall, Patrick; Boy, Ramiz; Broughton, Roy M.; Solano, Alejandro Aguilar; Esquivel, Marianelly; Parker, Jennifer; Fuente, Leonardo De La; Auad, Maria L.
Highlights: Alginate–chitosan fibers were prepared through wet spinning technique. Gelation occurred due to interaction between negatively charged alginate and positively charged chitosan. The incorporation of chitosan into the fibers improved their tensile properties. The in vitro release test indicated that the fibers are viable carriers of drugs. Fibers showed excellent inhibition of Escherichia coli growth. Abstract: The preparation of alginate–chitosan fibers, through wet spinning technique, as well as the study of their properties as a function of chitosan's molecular weight and retention time in the coagulation bath, is presented and discussed in this work. Scanning electron microscopy (SEM) revealed that the fibers presented irregular and rough surfaces, with a grooved and heavily striated morphology distributed throughout the structure. Dynamic mechanical analysis (DMA) showed that, with the exception of elongation at break, the incorporation of chitosan into the fibers improved their tensile properties. The in vitro release profile of sulfathiazole as a function of chitosan's molecular weight indicated that the fibers are viable carriers of drugs. Kinetic models showed that the release of the model drug is first-order, and the release mechanism is governed by the Korsmeyer–Peppas model. Likewise, fibers loaded with sulfathiazole showed excellent inhibition of Escherichia coli growth after an incubation time of 24 h at 37 °C.